Human Rights Violation Against the Indonesian Migrant Fisheries Crew in Chinese-Flagged Long Xing Vessel - Shalihah, Fithriatus; Nur, Muhammad (Yustisia, 2021)
This paper aimed to analyze human rights violations against migrant fishing boat crews with a case study on the Chinese-flagged Long Xing fishing boat. The research method used is empirical legal research using primary data and secondary data. The results showed that there had been human rights violations experienced by migrant fishing boat crews aboard the Chinese-flagged Long Xing fishing boat. These human rights violations have occurred since the pre-employment phase. The act of dumping the bodies of the crew members of Indonesian ships into the sea in the case of the Long Xing Ship violated the provisions of the ILO Seafarers Regulation Article 30 concerning protocol if the crew of the ship died, also violated Indonesia's national regulations, namely the Minister of Transportation Regulation No. 84 of 2013 Article 18 concerning the protocol for repatriating the bodies of crew members. Therefore, Indonesia's Government needs serious improvements to protect Indonesian fishing boat crews by implementing legal protection regarding their rights both before, during, and after Indonesian migrant fishery crew members work abroad